July mean temperature and annual precipitation trends during the Holocene in the Fennoscandian tree-line area: pollen-based climate reconstructions - Seppä, Heikki; Birks, Harry John Betteley (The Holocene, 2001)
July mean temperature and annual precipipation during the last 9900 cal. yr BP were recon structed from pollen assemblages preserved in a sediment core from northern Finland. Quantitative recon structions were performed using a modern pollen-climate calibration model based on weighted-averaging partial least squares regression. The predictive ability of the model was evaluated against modern meteoro logical data using leave-one-out cross-validation. The prediction error for July mean temperature is c.1.0°C and for annual precipitation 340 mm. The July mean temperatures during the earliest Holocene were low, c.11.0°C, and annual precipitation was high, c. 600–800 mm. Between 8200 and 6700 cal. yr BP July mean temperatures reached their maxima, 12.5–13.0°C, which are c. 1.4–1.7°C higher than at present. At the same time precipitation decreased. During the late Holocene, July mean temperatures declined and the last 2000 years have been the coolest since the early Holocene. Precipitation has slightly increased. The spatial coherence between our results and of several other climate reconstructions from northern Europe indicates that the Holocene climate was strongly influenced by North Atlantic oceanic and atmospheric circulation patterns. We propose that the distinctly oceanic climate of the early Holocene was due to enhanced westerly (latitudinal) airflow which was replaced at c. 8200 cal. yr BP by a more meridional flow pattern and by the development of predominantly anticyclonic summer conditions.